2014
DOI: 10.1523/jneurosci.5419-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic NMDA Receptor Signaling Is Required for the Induction of Long-Term Depression in the Mouse Hippocampal CA1 Region

Abstract: Previous studies have provided strong support for the notion that NMDAR-mediated increases in postsynaptic Ca2ϩ have a crucial role in the induction of long-term depression (LTD). This view has recently been challenged, however, by findings suggesting that LTD induction is instead attributable to an ion channel-independent, metabotropic form of NMDAR signaling. Thus, to explore the role of ionotropic versus metabotropic NMDAR signaling in LTD, we examined the effects of varying extracellular Ca 2ϩ levels or bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 34 publications
7
57
0
Order By: Relevance
“…This approach allowed us to assess the synapse-specific contributions of preNMDARs to tLTD and to overcome the possibility that channel-blocking NMDAR antagonists may not always block LTD induction (Nabavi et al, 2013; but see Babiec et al, 2014). While our genetic approach demonstrated a role for preNMDARs in L4-L2/3 tLTD and avoided the potential confound of using an open-channel NMDAR antagonist, we also found that reducing ion flux through NMDARs with MK-801 blocked tLTD mediated by preNMDARs at L4-L2/3 synapses (Figure 2) as well as tLTD mediated by postsynaptic NMDARs at L2/3-L2/3 synapses (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed us to assess the synapse-specific contributions of preNMDARs to tLTD and to overcome the possibility that channel-blocking NMDAR antagonists may not always block LTD induction (Nabavi et al, 2013; but see Babiec et al, 2014). While our genetic approach demonstrated a role for preNMDARs in L4-L2/3 tLTD and avoided the potential confound of using an open-channel NMDAR antagonist, we also found that reducing ion flux through NMDARs with MK-801 blocked tLTD mediated by preNMDARs at L4-L2/3 synapses (Figure 2) as well as tLTD mediated by postsynaptic NMDARs at L2/3-L2/3 synapses (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…This shift to LTD does not occur when the NMDAR is blocked by an antagonist blocking the glutamate binding site, suggesting that the induction of NMDAR-dependent LTD relies on metabotropic NMDAR function, rather than on ionotropic NMDAR function with calcium influx through the channel [46,47]. Provided that metobotropic NMDA-dependent LTD exists in mature dentate granule cells, it is thus a likely scenario that this LTD is unmasked when the inhibitory control of the ionotropic NMDAR function is strong, and newborn granule cells are depleted.…”
Section: Discussionmentioning
confidence: 99%
“…Studies supporting an ion-flow-independent role for NMDARs in LTD (4-7) and other processes (7-13) stand in contrast to studies proposing that flow of Ca 2+ through NMDAR is required for LTD (14) (see ref. 15 for additional references). An important test of an ion-flow-independent model would be to measure directly signaling actions by NMDARs in the absence of ion flow.…”
Section: Long-term Depression | Ltd | Nmdar-pp1 Fret | Nmdar-camkii Imentioning
confidence: 99%